Integrating Lev Vygotsky’s Sociocultural Theory into Online Instruction: A Case Study - Osias Kit T. Kilag; Desiree Ann F. Maghanoy; Kristie Rose D. Dela Calzada-Seraña; Ruby B. Ponte (Journal of Learning on History and Social Sciences, 2024)
This case study examines the integration of Sociocultural Theory (SCT) into an online course and its impact on learning outcomes and sense of community among senior high school students. Data were collected through pre- and post-course surveys, semi-structured interviews with the instructor and a subset of five students, and observations of the course discussions. Thematic analysis revealed four major themes: increased engagement and participation, improved learning outcomes, enhanced sense of community, and challenges and limitations. The findings suggest that integrating SCT principles into online instruction can lead to increased engagement and participation, improved learning outcomes, and enhanced sense of community among learners. The study also highlights some challenges and limitations, such as the need for clear guidelines and support for both instructors and students, and the importance of addressing the digital divide and ensuring access to technology and resources. This study contributes to the growing body of research on the application of SCT to online instruction and provides insights that can inform the development of effective online instructional practices that support learners' social and cultural experiences. The implications of this study are relevant for educators and instructional designers who seek to enhance the quality of online instruction and promote effective and inclusive learning environments. Future research in this area may further explore the impact of SCT on other aspects of online learning, such as motivation, self-regulated learning, and intercultural communication. Additionally, research can investigate the potential of integrating SCT into other educational contexts, such as blended or hybrid learning environments.